2014
DOI: 10.1186/1471-2105-15-49
|View full text |Cite
|
Sign up to set email alerts
|

Gene selection for cancer identification: a decision tree model empowered by particle swarm optimization algorithm

Abstract: BackgroundIn the application of microarray data, how to select a small number of informative genes from thousands of genes that may contribute to the occurrence of cancers is an important issue. Many researchers use various computational intelligence methods to analyzed gene expression data.ResultsTo achieve efficient gene selection from thousands of candidate genes that can contribute in identifying cancers, this study aims at developing a novel method utilizing particle swarm optimization combined with a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…They evaluated the performance of the proposed method (PSODT) and compare it with other algorithms of classification, such as SOM, DT (C4.5), neural networks, SVM, and Naive Bayes. The results have shown that PSODT provides better than the others methods [44].…”
Section: Classification Techniquesmentioning
confidence: 67%
“…They evaluated the performance of the proposed method (PSODT) and compare it with other algorithms of classification, such as SOM, DT (C4.5), neural networks, SVM, and Naive Bayes. The results have shown that PSODT provides better than the others methods [44].…”
Section: Classification Techniquesmentioning
confidence: 67%
“…This integrated algorithm involves a genetic algorithm and correlation-based heuristics for data preprocessing and data mining for making predictions. Chen et al (2014) suggested to achieved efficient gene selection from thousands of candidate genes that can contribute in identifying cancers, this study aims at developing a novel method utilizing particle swarm optimization combined with a decision tree as the classifier. The study also compares the performance of their proposed method with other well-known benchmark classification methods (support vector machine, selforganizing map, and backpropagation neural network).…”
Section: Literature Surveymentioning
confidence: 99%
“…This new invention of biological technology has not only brought a great impact toward biological domain but has given immense challenges to computer scientists in order to handle big data issues. Hence, even microarray technology offers a new platform in investigating cancer, analyzing large-scale of gene expression data generated by this device is not an easy task [3]. Microarray data analysis is a fast-growing since this device can be used to measure global expression of genes simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Microarray data analysis is a fast-growing since this device can be used to measure global expression of genes simultaneously. However, analyzing and interpreting large scale of gene expression data remain a challenging issue due to their innate nature of "high dimensional low sample size" [3,4]. Microarray data mainly involved thousands of genes, n in a very small size sample, p. In addition, this data is often overwhelmed, over fitting and confused by the complexity of data analysis [5,6].…”
Section: Introductionmentioning
confidence: 99%